Assessment and learning: fields apart? - Baird, J; Andrich, D; Hopfenbeck, T; Stobart, G (Taylor and Francis, 2017)
Educational assessments define what aspects of learning will formally be given credit and therefore have a huge impact upon teaching and learning. Although the impact of high-stakes national and international assessments on teaching and learning is considered in the literature, remarkably, there is little research on the connection between theories of learning and educational assessments. Given the voluminous assessment that takes place annually in systematic ways in most many nations, it is surprising that more has not been gained from these assessments in the development of theories of learning and vice versa. In this article we consider both theories of learning and assessment and draw the main message of the article, that if assessments are to serve the goals of education, then theories of learning and assessment should be developing more closely with each other. We consider fundamental aspects of assessment theory, such as constructs, unidimensionality, invariance and quantifiability, and in doing so, we distinguish between educational and psychological assessment. Second, we show how less traditionally considered cases of a) international assessments and b) Assessment for Learning affect student learning. Through these cases we illustrate the otherwise somewhat theoretical discussion in the article. We argue that if assessment is to serve the learning goals of education, then this discussion on the relationship between assessment and learning should be developed further and be at the forefront of high-stakes, large-scale educational assessments.